Determinants of Firm Value: With Corporate Social Responsibility (CSR) as Moderation (Case Study of Mining Companies Listed on the Indonesia Stock Exchange for the 2019-2021 Period) - Karina Putri; Yuliusman; Wiwik Tiswiyanti (East Asian Journal of Multidisciplinary Research, 2023)
This study aims to determine the effect of ownership structure and ISO 14001 certification on firm value with CSR as a moderating variable. The population of this study includes all mining companies listed on the IDX for the 2019-2021 period. The sampling technique used was purposive sampling. The research population data were 49 companies and a sample of 18 companies was obtained. The analysis technique used is to use Moderated Regression Analysis. The results showed that managerial ownership has no effect on firm value. Institutional ownership affects firm value. ISO 14001 certification affects firm value. CSR cannot moderate the relationship between managerial ownership and firm value. CSR can moderate the relationship between institutional ownership and firm value. CSR cannot moderate the relationship between ISO 14001 certification and firm value.